Husnuzhan-based Islamic positive psychology training to foster happiness among new santriwati - Fadhila, Mahdia; Hairina, Yulia; Aliffia, Dhiza (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examined the preliminary psychological impact of Husnuzhan-Based Islamic Positive Psychology Training on happiness among new female students (santriwati) at Darul Hijrah Islamic Boarding School, South Kalimantan. Grounded in the Islamic concept of husnuzhan—maintaining positive assumptions toward Allah, oneself, and others—the training was designed to support emotional regulation and positive cognitive–spiritual appraisal during the early adaptation period in a pesantren environment. Using a pilot quasi-experimental design with a one-group pretest–posttest approach, 17 new santriwati were purposively selected from 107 students who completed the PERMA-Profiler Scale, based on relatively lower happiness scores as well as their availability and willingness to participate. The intervention consisted of four sessions incorporating psychoeducation, reflective exercises, relaxation techniques, and Islamic positive self-talk practices. Quantitative data were analyzed using a paired-samples t-test, while qualitative data from reflective worksheets and interviews were examined through content analysis. The results indicated a strong correlation between pre-test and post-test scores (r = 0.826, p < 0.001), but the increase in happiness scores was not statistically significant, t(16) = 0.81, p = 0.43, with a small effect size (Cohen’s d = 0.20). Qualitative findings revealed early psycho-spiritual changes, including increased emotional calmness, gratitude, optimism, and greater trust in Allah when interpreting daily challenges. Overall, the findings suggested that Husnuzhan-Based Islamic Positive Psychology Training is feasible as a foundational psycho-spiritual intervention for new santriwati, supporting emotional stabilization, adaptive religious coping, and spiritual character formation, although further studies with larger samples and longitudinal designs are needed to examine its long-term effectiveness.